ANALISIS PEMASARAN SYARIAH TERHADAP PENJUALAN ALAT KONTRASEPSI DI MINIMARKET KECAMATAN BANDUNG WETAN KOTA BANDUNG - Lia Yulia; Popon Srisusilawati; Ivan Wahyudi (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2019)
Islam forbids selling goods that are misused. Contraception is an item that is sold freely to unmarried people, so there is a lot of abuse of contraception. Based on the background of the problem, the formulation of the problem is as follows: How is sharia marketing ethics regarding contraception, How is the practice of buying and selling contraception in Indomaret, Bandung Wetan Subdistrict, How is the syariah marketing ethics analysis of contraceptive sales in Indomaret, Bandung Wetan District. This study aims to determine how Islamic marketing ethics regarding contraception, the practice of buying and selling contraception in Indomaret, Bandung Wetan Subdistrict, and sharia marketing ethics analysis on the sale of contraceptives in Indomaret, Bandung Wetan District. The research method used is a descriptive analytical method qualitatively. The data source used primary data is data obtained directly from the Indomaret cashier through interviews. Based on the results of the study, conclusions were obtained that it turned out that Indomaret sold contraceptives not in accordance with Islamic marketing ethics and was not in accordance with the purpose of contraceptive procurement, because from the interviews with Indomaret cashiers that they strongly safeguarded consumers' privacy and did not want to know about consumer condoms use or for whom the condom was purchased.